PENGARUH MANAJEMEN LINGKUNGAN ISLAMI TERHADAP PENINGKATAN PRESTASI BELAJAR SISWA DI SEKOLAH DASAR ISLAM AL-FURQON KABUPATEN KARAWANG - Ajat Rukajat; Masykur H.Mansyur; Nabilhaibah Qoriy Hakiki (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the influence of Islamic environmental management on improving students' academic achievement at Al-Furqon Islamic Elementary School in Karawang Regency. A learning environment managed with Islamic values is believed to create a religious, comfortable, and conducive atmosphere, which positively impacts students' cognitive, affective, and psychomotor development. The study employs a quantitative approach with a correlational method. Data collection techniques include questionnaires and documentation. The analysis results show a significant influence of Islamic environmental management—including planning, organizing, actuating, and controlling—on students' academic achievement. This research highlights the importance of integrating Islamic values into school environmental management as a strategy to enhance the quality of elementary education and shape students with noble character.